2011
DOI: 10.1007/s00595-010-4423-9
|View full text |Cite
|
Sign up to set email alerts
|

Matrine attenuates endotoxin-induced acute liver injury after hepatic ischemia/reperfusion in rats

Abstract: Matrine attenuates endotoxin-induced acute liver injury after HIR mainly by its anti-inflammatory and antioxidative activities, and has little inhibitory effect on cell apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The serum samples were stored at −20°C. Serum ALT and AST levels were determined by an automated biochemical analyzer (Toshiba, Tokyo, Japan) [14]. ALT and AST in serum samples were expressed in units/l.…”
Section: Serum Liver Function Assaymentioning
confidence: 99%
“…The serum samples were stored at −20°C. Serum ALT and AST levels were determined by an automated biochemical analyzer (Toshiba, Tokyo, Japan) [14]. ALT and AST in serum samples were expressed in units/l.…”
Section: Serum Liver Function Assaymentioning
confidence: 99%
“…The resultant cardiac cell death induces the loss of cardiac contractile units and subsequently provokes cardiac remodeling, thereby playing an important role in the pathophysiological processes of DCM [2,7] . The clinical application of the traditional Chinese herb, Sophora alopecuroides L, has a long history in China of effectively treating various diseases, including chronic liver disease, heart failure, and hypertension [8,9] . The herb's clinical effects were believed to be dependent on its active molecule, C 15 H 24 N 2 O, an alkaloid also known as matrine ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Their structures belong to the quinazolines, and the molecular skeleton can be regarded as the impurity of the two quinazoline and pyridine rings (Pan et al, 2015). A number of pharmacological studies and clinical practice have shown that, matrine can be used in the treatment of hepatitis (Ma et al, 2013), liver fibrosis (Yu et al, 2014), arrhythmia (Xin & Liu, 2011) and ischemia (Zhang et al, 2011). At the same time, matrine has clear functions in calming, relieving pain, regulating body temperature, enhancing myocardial function, treating hypertension and even resisting virus (Zhou et al, 2008).…”
Section: Discussionmentioning
confidence: 99%